Adverse childhood experiences influence white matter microstructure in patients with bipolar disorder. Issue 14 (27th March 2014) - Benedetti, F.; Bollettini, I.; Radaelli, D.; Poletti, S.; Locatelli, C.; Falini, A.; Smeraldi, E.; Colombo, C.
Abstract : Background: Bipolar disorder (BD) is associated with adverse childhood experiences (ACE), which worsen the lifetime course of illness, and with signs of widespread disruption of white matter (WM) integrity in adult life. ACE are associated with changes in WM microstructure in healthy humans. Method: We tested the effects of ACE on diffusion-tensor imaging (DTI) measures of WM integrity in 80 in-patients affected by a major depressive episode in the course of BD. We used whole-brain tract-based spatial statistics in the WM skeleton with threshold-free cluster enhancement of DTI measures of WM microstructure: axial, radial and mean diffusivity, and fractional anisotropy. Results: ACE hastened the onset of illness. We observed an inverse correlation between the severity of ACE and DTI measures of axial diffusivity in several WM fibre tracts contributing to the functional integrity of the brain and including the corona radiata, thalamic radiations, corpus callosum, cingulum bundle, superior longitudinal fasciculus, inferior fronto-occipital fasciculus and uncinate fasciculus. Conclusions: Axial diffusivity reflects the integrity of axons and myelin sheaths, and correlates with functional connectivity and with higher-order abilities such as reasoning and experience of emotions. In patients with BD axial diffusivity is increased by lithium treatment. ACE might contribute to BD pathophysiology by hampering structural connectivity in critical cortico-limbic networks.